Reposisi Hakikat Beragama di tengah Kemajemukan Indonesia - Didimus Sutanto B Prasetya; Candra Gunawan Marisi (JURNAL TEOLOGI GRACIA DEO, 2022)
The philosophy of the state of the Indonesian people is Pancasila with the first principle " Belief in One Supreme God" meaning that Indonesian citizens are human beings who believe in God in the diversity of beliefs and religions in Indonesia. It is ironic that as a country based on God, religion has become an identity to be proud of, but the moral decline is also shown. This study aims to find and reposition the nature of religion in realizing religious moderation in Indonesia's pluralism. The method in this research is descriptive qualitative, where data is collected through research literature in the form of books and journals related to the topic of the problem. Religion should be placed in a private space. This restores religion as the most essential human right, there is no majority or minority, every individual has the same rights. Based on this understanding, religion and the nature of religion must be positioned in the privacy of each individual, so that religion is not indicated by its level of religiosity alone but rather to its spiritual level, personal relationship with God. AbstrakFalsafah bangsa Indonesia adalah Pancasila dengan sila pertama “Ketuhanan Yang Maha Esa” artinya bahwa warga negara Indonesia merupakan manusia yang ber-Tuhan dalam kebera-gaman kepercayaan dan agama di Indonesia. Ironis sebagai negara yang berlandaskan Ketuhanan, agama menjadi suatu identitas yang dibanggakan namun kemerosotan moral juga dipertontonkan. Penelitian ini bertujuan untuk menemukan dan memposisikan kembali hakikat beragama dalam mewujudkan moderasi beragama di tengah kemajemukan Indonesia. Metode dalam penelitian ini adalah kualitatif deskriptif, di mana data dikumpulkan melalui literatur research yang berupa buku maupun jurnal yang berkaitan dengan topik permasalahan tersebut. Agama harus ditem-patkan pada ruang pribadi. Hal ini mengembalikan agama sebagai hak asasi manusia yang paling hakiki, tidak ada pemeluk mayoritas ataupun pemeluk minoritas, setiap individu memiliki hak yang sama. Berdasar dari pemahaman tersebut, agama dan hakikat beragama harus diposisikan pada ruang privasi setiap individu, sehingga agama bukanlah ditunjukkan dengan tingkat religio-sitasnya semata melainkan lebih kepada tingkat spiritualnya, hubungan pribadi dengan Tuhannya.